The impact of German public support transfers on firm finance: Evidence from the Covid-19 crisis - Leo Gärtner; Philipp Marek (Deutsche Bundesbank, 2022)
The economic policy response to COVID-19 lockdowns included a variety of measures. Their effects on non-financial firms, however, remain unclear. To shed light on the effect of transfers, we investigate the effect of German emergency aid transfers (November-December aid), a program designed for small and medium sized firms. Using novel survey data, we exploit variation in application status to estimate its effects on the financial situation of firms. We distinguish between firms that had already used aid transfers and those firms with a pending application. Our results show that firms substantially benefited from the November-December aid program. The provision of transfers improved liquidity and access to credit for distressed firms, while decreasing credit demand. The estimates suggest that firms that had received an approval of their application for November-December aid faced a 5-percentage point lower probability of being confronted with a low liquidity buffer. We also find strong evidence, that firms substituted aid with credit, since firms with a pending application status faced an 8-percentage point higher likelihood of starting credit negotiations. Moreover, the provision of November-December aid improved the creditworthiness of firms. We can show that receiving these transfers increased the probability of obtaining a loan at the desired conditions by 14 to 18 percentage points.
Keywords: C14; G32; G33; H84; L25; J68; 330; SMEs; emergency aid; treatment effects; COVID-19; firm finance